Evaluation Of Diisocyanates And Their Metabolites In Selected Iranian Polyurethane Factories - Mirmohammadi, Mirtaghi (2010)

(untitled)
In this thesis the concentration of diisocyanates namely hexamethylene diisocyanate (HDI), methylene diphenyl diisocyanate (MDI) and toluene diisocyanate (TDI) in indoor air samples and their respective metabolites hexamethylene diamine (HDA), methylene dianiline (MDA) and toluene diamine (TDA) found in workers’ urine were measured in fifteen polyurethane factories located in the Tehran province, Karaj city and Mazandaran province in Iran. Measurement of isocyanate concentration was performed using the NIOSH 5522 method. Measurement was conducted over three daily working shifts in fifteen factories with a total of three hundred air samples. Psychrometric parameters (indoor air temperature and relative humidity), workplace dimension and altitude factors were evaluated to correlate to the diisocyanate pollution level. The association between diisocyanates and health effects and specific sensitisation was also studied. The findings of this study demonstrated that HDI, MDI and TDI were dominant in frequency of occurrence and showed the highest exposure levels when compared to NIOSH, OSHA and ACGIH standards and some other studies. The correlation between psychrometric parameters and diisocyanate concentration was determined and the results showed that, relative humidity and dry bulb temperature have positive significant relationship.